Distortion Product Otoacoustic Emissions (DPOAEs) In Tinnitus Patients - Alshabory, Hend F.; Gabr, Takwa A.; Kotait, Mona A. (International Archives of Otorhinolaryngology, 2021)
Introduction Tinnitus is the perception of sound in the absence of external sound stimulation. There is a general agreement that it is a direct consequence of irreversible and permanent cochlear damage.Objectives The present work is designed to study the distortion product otoacoustic emissions (DPOAEs) in tinnitus patients with normal hearing in comparison with normal hearing control and to study any possible correlation between DPOAEs recording and patients' complaints.Methods The present study included 80 subjects divided into 2 groups: Control group: consisted of 30 normal-hearing adults not complaining of tinnitus and Study group: consisted of 50 normal-hearing adults complaining of tinnitus. The methodology includes full audiological history, otoscopic examination, basic audiological evaluation, DPOAEs including both DP-gram and DPOAEs input/output functions.Results Basic audiological evaluation showed within normal hearing sensitivity in both groups, however, with significant higher hearing thresholds in tinnitus patients at all frequency ranges. The Tinnitus Handicap Inventory Questionnaire showed mean scores of 35.2 ± 16.9 in the study group. The DP-gram showed higher amplitudes in the control group when compared with tinnitus patients. The DPOAEs input-output functions at different frequencies (1, 2, 4 and 6kHz) also showed higher amplitudes at all frequencies and different input levels. The slope of the I/O function tends to be steeper in tinnitus cases.Conclusion Patients with tinnitus might have neural dysfunction at either the level of the cochlea, as shown in reduced DPOAE levels, and changes in the normal DP-I/O function recorded in the present work.
Keywords: tinnitus; otoacoustic emissions; cochlear outer hair cells